Management of Land and Building Assets in Tolotio Village, Tibawa District, Gorontalo Regency - Dian Fitriani Karim; Sri Lestari Gintulangi; Suriya Suleman (Journal La Bisecoman, 2022)
This study aims to determine the Management of Land and Building Assets in Tolotio Village, Tibawa District, Gorontalo Regency. The research method uses a qualitative type. The results of the study indicate that the management of land and building assets in Tolotio Village, Tibawa District, Gorontalo Regency has not been running well, where 1 (one) of 4 (four) indicators measured, namely the planning indicator is optimal, namely the existence of planning activities by the Tolotio Village Government together with other stakeholders. those in Tolotio Village plan for the village's needs every year which are contained in the Village Government Work Plan (RKPDes). Meanwhile, 3 (three) other indicators measured, namely organization, direction and supervision were not optimal. This can be seen from the process of administering and reporting land and building assets that have not organized all land and building assets in Tolotio Village and the inability of the Tolotio Village Government in directing and supervising land and building assets into productive physical resources.